2013
DOI: 10.1073/pnas.1307321110
|View full text |Cite
|
Sign up to set email alerts
|

Skin-specific expression of IL-33 activates group 2 innate lymphoid cells and elicits atopic dermatitis-like inflammation in mice

Abstract: Transgenic mice expressing the mouse interleukin 33 (IL-33) gene driven by a keratin 14 promoter were generated. The skin-selective expression of the IL-33 gene was enhanced, and intense immunofluorescence for IL-33 was evident in the nuclei of the epidermis. Spontaneous itchy dermatitis developed in those mice at 6-8 wk of age in specific pathogen-free conditions. In the lesional skin, the epidermis was thickened and the eosinophils were infiltrated with increased expression of the eosinophil peroxidase and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
341
1
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 382 publications
(353 citation statements)
references
References 33 publications
5
341
1
6
Order By: Relevance
“…IL-33 expression is also enhanced in human ACD skin (21). More importantly, skin-specific expression of IL-33 can elicit atopic dermatitis-like inflammation and scratching behavior in mice (22). In the present study, we therefore investigated the possible involvement of this cytokine in itch caused by poison ivy ACD.…”
Section: Resultsmentioning
confidence: 91%
“…IL-33 expression is also enhanced in human ACD skin (21). More importantly, skin-specific expression of IL-33 can elicit atopic dermatitis-like inflammation and scratching behavior in mice (22). In the present study, we therefore investigated the possible involvement of this cytokine in itch caused by poison ivy ACD.…”
Section: Resultsmentioning
confidence: 91%
“…In the skin, ILC2s have been shown to be predominantly regulated by TSLP during AD-like disease (Kim et al 2013a). However, recent studies showed that IL-25 and IL-33 may also have relevant roles in AD-like inflammation (Imai et al 2013;Salimi et al 2013). Collectively, whether IL-25, IL-33, or TSLP is the dominant cytokine for the activation and/or elicitation of ILC2s at different barrier surfaces remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Further, skin-associated ILC2s could directly induce AD-like pathology and T H 2 cell responses in vivo (Kim et al 2013a). A more recent study confirmed the presence of ILC2s in murine skin and used transgenic mice overexpressing IL-33 under a keratin 14 promoter to show that IL-33 expression can also drive AD-like inflammation and the expansion of ILC2s in the skin (Imai et al 2013). Recently, Salimi et al (2013) confirmed that skin ILC2s are dependent on TSLP in C57BL/6 mice and found that there is partial dependence on both IL-25 and IL-33 in the development of skin ILC2 responses in BALB/ c (but not C57BL/6) mice during AD-like inflammation.…”
Section: Ilc2s In the Skin Atopic Dermatitismentioning
confidence: 97%
“…These cells control eosinophil homeostasis in blood and adipose tissue (18,19) and produce extremely high amounts of the type-2 cytokines IL-5 and IL-13 in response to IL-33 (14)(15)(16). ILC2s also play important roles in allergic airway inflammation (20)(21)(22)(23)(24), atopic skin disease (25)(26)(27)(28), helminth infection in the intestine (11,12,(14)(15)(16), and influenza virus infection in the lungs (29,30).…”
mentioning
confidence: 99%